High frequency oscillations relate to cognitive improvement after epilepsy surgery in children. Issue 5 (May 2020) - Sun, Dongqing; van 't Klooster, Maryse A.; van Schooneveld, Monique M.J.; Zweiphenning, Willemiek J.E.M.; van Klink, Nicole E.C.; Ferrier, Cyrille H.; Gosselaar, Peter H.; Braun, Kees P.J.; Zijlmans, Maeike
Highlights: Postoperative cognitive improvement relates to the removal of fast ripple generating tissue. Postoperative decrease of ripples on spikes is associated with cognitive improvement. High frequency oscillations are potential predictive markers for postoperative cognitive outcome. Abstract: Objective: To investigate how high frequency oscillations (HFOs; ripples 80–250 Hz, fast ripples (FRs) 250–500 Hz) and spikes in intra-operative electrocorticography (ioECoG) relate to cognitive outcome after epilepsy surgery in children. Methods: We retrospectively included 20 children who were seizure free after epilepsy surgery using ioECoG and determined their intelligence quotients (IQ) pre- and two years postoperatively. We analyzed whether the number of HFOs and spikes in pre- and postresection ioECoGs, and their change in the non-resected areas relate to cognitive improvement (with ≥ 5 IQ points increase considered to be clinically relevant (=IQ+ group) and < 5 IQ points as irrelevant (=IQ− group)). Results: The IQ+ group showed significantly more FRs in the resected tissue (p = 0.01) and less FRs in the postresection ioECoG (p = 0.045) compared to the IQ− group. Postresection decrease of ripples on spikes was correlated with postoperative cognitive improvement (correlation coefficient = −0.62 with p = 0.01). Conclusions: Postoperative cognitive improvement was related to reduction of pathological HFOs signified by removing FR generating areas with subsequently less residual FRs, and decrease of ripples on spikes in the resection edge of the non-resected area. Significance: HFOs recorded in ioECoG could play a role as biomarkers in the prediction and understanding of cognitive outcome after epilepsy surgery.